2021
DOI: 10.3389/fpsyg.2021.725060
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Entrepreneurship to the Social Integration of People Intellectual Disabilities: A Case Study Based on the Analysis of Social Networks

Abstract: In an environment characterized by high unemployment rates among people with disabilities, the objective of the present work is to analyze entrepreneurship as a labor option which fully inserts people with intellectual disabilities (PwID) into their societies. In order to carry out this research, a case study methodology based on social network analysis has been adopted, given the nature of the variables analyzed. The results indicate that the fact of having managed to start up the company has been an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Opposite to this prejudice, there are data that highlight how the exclusion of PWDs from the workforce has costs for society, overall in terms of their productive potential ( Calderón-Milán et al, 2020 ). Other studies confirmed that people with intellectual disability can be successfully involved in the process of start-up a company, with also benefits the social relations ( Barba-Sánchez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
“…Opposite to this prejudice, there are data that highlight how the exclusion of PWDs from the workforce has costs for society, overall in terms of their productive potential ( Calderón-Milán et al, 2020 ). Other studies confirmed that people with intellectual disability can be successfully involved in the process of start-up a company, with also benefits the social relations ( Barba-Sánchez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, corporate social goal orientation has an inseparable dependency relationship with various subjects in the external system, and the establishment of external core stakeholder relations is a key factor conducive to the enterprise's own development as well as the effective allocation of scarce social resources. Second, maintaining a positive relationship quality with core stakeholders such as society, meeting their needs, and solving social problems, such as employment, entrepreneurship, and pension are conducive to market and social integration (Barba-Sánchez et al, 2021). Although some 10.3389/fpsyg.2022.942294 studies have explored innovation-driven corporate value from the perspective of profitability (Jin et al, 2016;Xia and Liu, 2021), they have ignored the dynamics of corporate social goal orientation behaviors at the micro-level and how stakeholder relationships promote its development.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have recognized the important role of stakeholder relationships in the realization of enterprise value, in the theoretical analysis, it is found that entrepreneurs who are aware of social responsibility seek stakeholder relationships ( Barba-Sánchez et al, 2021 ) and maintain a positive relationship quality with core stakeholders such as society, which is conducive to solving social problems such as environmental protection and employment. However, the existing research on stakeholder relationships takes a theoretical view that does not consider how such relationships function in practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations